Persistent red-tagging in the Philippines as violation of the principle of distinction in international humanitarian law (Philippine Law Journal, 2022)
Red-tagging by state forces is a strategy employed in the context of the longstanding conflict between the Philippine govemment and the Communist Party of the Philippines-New People's Ary (CPP- NPA). As a result, left-leaning and dissenting individuals and groups-who take no active part in hostilities-become targets of attacks and acts of violence. This Article examines how the conflict between the Philippine goverment and the CPP-NPA may be classified as a Common Article 3 non-international armed conflict ("NIAC") where intemational humanitarian law ("THL") finds application. By making the finding that Common Article 3 may apply in this context, the Article theorizes that red-tagging violates the principle of distinction in IHL through the targeting of civilians and the deliberate blurring of lines between combatants and civilians performing no combat functions. Finally, it proposes a tum to human rights law, civil remedies, and protective writs as a remedy for civilians being targeted through red-tagging.